Mahabalella pernambucana, a new hyphomycete from Brazil with notes on its phylogenetic positioning - Wanderson Luiz Tavares; Marcela Alves Barbosa; Rafael F. Castañeda-Ruiz; Elaine Malosso (Acta Botânica Brasílica, 2023)
ABSTRACT A new species of Mahabalella B. Sutton & S. D. Patil was isolated from decaying leaves of an unidentified plant, during a survey in the Charles Darwin Ecological Refuge in Igarassu, Pernambuco, Brazil, in June 2018. The new species is morphologically distinguishable from the other Mahabalella species by the size of their conidia, conidiogenous cells and setae. In this study, the morphological descriptions, illustrations and cultural characteristics for Mahabalella pernambucana are provided, as well as a key to species of this genus. Total DNA from the isolate was extracted, and four genes were partially sequenced (nLSU, ITS cluster, TEF1 alpha, and beta tubulin). Based on the nLSU analysis, the phylogenetic position of the new species was determined within the Sordariomycetes, Ascomycota, as a sister genus to Neotracylla, in the Tracyllaceae family.